The Effects of Medroxyprogesterone Acetate on Apoptosis of CD34+ Cells - Aydin, Fazil; Ozdemir, Feyyaz; Kavgaci, Halil; Yilmaz, Mustafa; Karti, Sami (Chemotherapy (Basel), 2003)
Background: Medroxyprogesterone acetate (MPA) is widely used in oncology practice, especially in the treatment of gynecological malignancies and cachexia of cancer. Some studies have demonstrated that high-dose MPA might reduce hematological toxicity in patients receiving chemotherapy for solid tumors. The underlying mechanism of this action is still unknown. We aimed to investigate the in vitro effects of MPA on CD34+ cells. Methods: We investigated the in vitro effects of two different doses of MPA (10 and 100 ng/ml) on acidic pH-induced apoptosis of CD34+ cells derived from 12 healthy volunteers. Results: Compared with the control group, we found that MPA at the dose of 100 ng/ml has a negative effect on apoptosis (6.7 ± 3.8 and 12.5 ± 5.0% apoptosis, respectively; p = 0.038) and a positive effect on the number of CD34+ cells (680 ± 294 and 350 ± 131 × 10 3 /ml, respectively; p = 0.009). Conclusion: Our results indicate that further studies are needed on larger populations in order to assess the relationship between MPA and its myeloprotective effect.